1995
DOI: 10.1084/jem.181.4.1319
|View full text |Cite
|
Sign up to set email alerts
|

Facultative role of germinal centers and T cells in the somatic diversification of IgVH genes.

Abstract: SummaryThe development of memory B cells takes place in germinal centers (GC) of lymphoid follicles where antigen-driven lymphocytes undergo somatic hypermutation and affinity selection, presumably under the influence of helper T cells. However, the mechanisms that drive this complex response are not well understood. We explored the relationship between GC formation and the onset of hypermutation in response to the hapten phosphorylcholine (PC) coupled to antigenic proteins in mice bearing different frequencie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
42
0
2

Year Published

1997
1997
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(47 citation statements)
references
References 53 publications
(75 reference statements)
3
42
0
2
Order By: Relevance
“…We confirm that T15 Id ϩ germinal centers can be found during a primary response to PC-KLH and that these germinal centers contain rearranged V H 1-DFL16.1-JH1 as reported by Miller et al (21). We extend their findings to demonstrate rearranged V 22-J 5 genes in the same pool of cells from single microdissected T15 ϩ germinal centers.…”
supporting
confidence: 76%
See 1 more Smart Citation
“…We confirm that T15 Id ϩ germinal centers can be found during a primary response to PC-KLH and that these germinal centers contain rearranged V H 1-DFL16.1-JH1 as reported by Miller et al (21). We extend their findings to demonstrate rearranged V 22-J 5 genes in the same pool of cells from single microdissected T15 ϩ germinal centers.…”
supporting
confidence: 76%
“…Reconstitution experiments have suggested that CD5 ϩ cells cannot form germinal centers (20), which might preclude T15 from accumulating mutations. The ability to participate in germinal center reactions remains unclear since Miller et al (21) have reported T15 Id ϩ germinal centers from which they could amplify the canonical V H 1-DFL16.1-JH1 rearrangement of T15; however, the presence of the T15 V 22-J 5 rearrangement was not formally demonstrated.…”
mentioning
confidence: 98%
“…l of a solution containing proteinase K (0.4 mg/ml) and incubated at 37°C overnight. The lysate was then subjected to two rounds of PCR, using two pairs of nested primers as described [25]. It has been shown that V H 1/DFL16.1/J H 1 are canonical rearrangements encoding anti-PC antibodies.…”
Section: Microdissecting Single Splenic Gc and Sequencing V(d)j Rearrmentioning
confidence: 99%
“…The presence of T cells and perhaps secondary FDCs would not be required for TI GCs to perform this function. Particular subsets of mature B cells might preferentially nucleate TI GCs, contributing to their unique characteristics (70). B cell receipt of inflammatory stimuli associated with pathogen infection might be required to make this response efficient, perhaps explaining the sporadic nature of TI GC responses induced by purified TI Ags in T cell-deficient mice (45).…”
Section: The Plasticity Of Gc Responses: Stepwise Development or Distmentioning
confidence: 99%